PEDIATRIC PYOGENIC SACROILIITIS: A RARE CASE REPORT - Shrestha, Bipan; Shrestha, Kishor Man; Pandey, Alok (Journal of Universal College of Medical Sciences, 2018)
Introduction: Pyogenic sacroiliitis accounts for 12% of all cases of septic arthritis with less than 200 cases reported in the English literature since the beginning of the twentieth century. Considerable delay between presentation and diagnosis is seen because of unusual presentation and diagnostic dilemma. Cultures of joint fluid usually grow Staphylococcus aureus. Magnetic resonance imaging has been found to be the most useful imaging modality in diagnosis. Being very uncommon disease in children, the key to successful management is early diagnosis in which computed tomography (CT), bone scans, and magnetic resonance imaging (MRI) findings play a crucial role. If the diagnosis is established promptly, most patients can be managed successfully with antimicrobial therapy with excellent prognosis. Most reported cases required prolonged antimicrobial therapy of six to nine weeks. Presented here is a child with pyogenic sacroiliitis managed at our hospital (Universal College of Medical Sciences Teaching Hospital-UCMSTH) and review of the literature on this relatively rare diagnosis. Journal of Universal College of Medical Sciences Vol. 6, No. 1, 2018, Page: 62-65